Produktivitas KWT Curug Kulon Melalui Adaptasi Teknologi Vertical Farming Modular - Oktarina, Freta; Diana, Rahmi Elsa; Djajadi, Arko (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: The reduction of green open spaces (RTH) in Indonesia’s urban areas has led to declining environmental quality and reduced potential for local food security. Tangerang Regency, with only 0.0137% of its area classified as RTH, faces serious challenges in providing productive spaces for its residents. Curug Kulon Urban Village exemplifies this green space crisis, where limited land has not been optimally utilized by the Melati Women Farmers Group (KWT). This community engagement program aims to increase land productivity and empower the local community by implementing modular vertical farming technology, drip irrigation systems, technical training, digital marketing, and educational activities. Method: The implementation methods include Focus Group Discussions (FGDs), hands-on training, the construction of vertical farming systems, and digital marketing assistance. Results: The results indicate a significant increase in the capacity of KWT members: more than 80% can now independently operate vertical farming systems, water-use efficiency has improved, and product promotion through social media is beginning to develop. In addition to the increased capacity of KWT members, local residents have begun participating in vertical farming through open training sessions. Furthermore, the tiered farming area serves as a micro RTH and an environmental learning space for the surrounding community. Conclusion: This program demonstrates that integrating simple technology with social and digital empowerment strategies can serve as a replicable urban farming model to optimize RTH in densely populated urban areas while simultaneously strengthening community food security.